2019
DOI: 10.1093/jn/nxz102
|View full text |Cite
|
Sign up to set email alerts
|

Grape Seed Proanthocyanidin Affects Lipid Metabolism via Changing Gut Microflora and Enhancing Propionate Production in Weaned Pigs

Abstract: Background It is not clear whether dietary grape seed proanthocyanidin (GSP) affects mammalian lipid metabolism via the gut microbiota. Objective The aim of this study was to evaluate the contribution of the gut microbiota to the effect of dietary GSP. Methods This study was divided into 3 separate experiments using Duroc × Landrace × Yorkshire pigs (50% male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 45 publications
1
65
0
Order By: Relevance
“…A possible mechanism proposed was that quercetin decreased the activity of microsomal TRIG transfer protein (MTP), resulting in the inhibition of intestinal apoB secretion ( 40 ). Moreover, proanthocyanidin was also reported to induce hypolipidemia by reducing TRIG in weaned pigs ( 41 ). Calcium and phosphorus are essential nutrients involved in many biological processes, and the studied wild blueberry pomaces have been reported to contain at least five times more Ca than in the used cranberry pomaces; however, both pomaces presented similar P content ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible mechanism proposed was that quercetin decreased the activity of microsomal TRIG transfer protein (MTP), resulting in the inhibition of intestinal apoB secretion ( 40 ). Moreover, proanthocyanidin was also reported to induce hypolipidemia by reducing TRIG in weaned pigs ( 41 ). Calcium and phosphorus are essential nutrients involved in many biological processes, and the studied wild blueberry pomaces have been reported to contain at least five times more Ca than in the used cranberry pomaces; however, both pomaces presented similar P content ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols in feed may increase the numbers of several bacteria, including Bacteroidetes , which tended to be higher with blueberry by-products in both ceca and cloacae as previously studied ( 15 ). These bacteria play an important role in breaking down complex carbohydrates to simpler compounds by encoding enzymes like polysaccharide lyases and glycoside hydrolases ( 41 ). BACI treatment resulted in lower abundances of Proteobacteria compared to berry pomace treatments, which correlates with an increased population of Firmicutes and Actinobacteria and probably higher BW .…”
Section: Discussionmentioning
confidence: 99%
“…It is also well known that high levels of TC, TG, and LDL in the blood are risk factors for atherosclerosis and that a high level of HDL could reduce the risk of cardiovascular diseases . A previous study demonstrated that total lipid and faecal bile acid excretion were significantly increased and that TC concentration in blood was effectively reduced by intervention of grape seed proanthocyanidin . Therefore, our observations suggested that LIP‐1 has a significant positive effect on enhancing lipid metabolism and that ME LIP‐1 was particularly effective.…”
Section: Discussionmentioning
confidence: 51%
“…20 A previous study demonstrated that total lipid and faecal bile acid excretion were significantly increased and that TC concentration in blood was effectively reduced by intervention of grape seed proanthocyanidin. 21 Therefore, our observations suggested that LIP-1 has a significant positive effect on enhancing lipid metabolism and that ME LIP-1 was particularly effective. Liver is usually considered to be the main organ to regulate the lipid metabolism and blood lipid levels.…”
Section: Discussionmentioning
confidence: 64%
“…Diets rich in fat and carbohydrates or low in fiber have all been linked to gut dysbiosis. Diets that include food from a variety of sources, including foods rich in plant pigments (16), are protective against dysbiosis. While a Western diet that is high in fats may be tolerable for some people, it can exacerbate underlying problems in others.…”
Section: Introductionmentioning
confidence: 99%